The casein kinase MoYck1 regulates development, autophagy, and virulence in the rice blast fungus. Issue 1 (1st January 2019) - Shi, Huan-Bin; Chen, Nan; Zhu, Xue-Ming; Su, Zhen-Zhu; Wang, Jiao-Yu; Lu, Jian-Ping; Liu, Xiao-Hong; Lin, Fu-Cheng
ABSTRACT: Casein kinases are serine/threonine protein kinases that are evolutionarily conserved in yeast and humans and are involved in a range of important cellular processes. However, the biological functions of casein kinases in the fungus Magnaporthe oryzae, the causal agent of destructive rice blast disease, are not characterized. Here, two casein kinases, MoYCK1 and MoHRR25, were identified and targeted for replacement, but only MoYCK1 was further characterized due to the possible nonviability of the MoHRR25 deletion mutant. Disruption of MoYCK1 caused pleiotropic defects in growth, conidiation, conidial germination, and appressorium formation and penetration, therefore resulting in reduced virulence in rice seedlings and barley leaves. Notably, the MoYCK1 deletion triggered quick lipidation of MoAtg8 and degradation of the autophagic marker protein GFP-MoAtg8 under nitrogen starvation conditions, in contrast to the wild type, indicating that autophagy activity was negatively regulated by MoYck1. Furthermore, we found that HOPS (homotypic fusion and vacuolar protein sorting) subunit MoVps41, a putative substrate of MoYck1, was co-located with MoAtg8 and positively required for the degradation of MoAtg8-PE and GFP-MoAtg8. In addition, MoYCK1 is also involved in the response to ionic hyperosmotic and heavy metal cation stresses. Taken together, our results revealed crucial roles of the casein kinase MoYck1 in regulating development, autophagy and virulence in M. oryzae .